Hubungan Pola Asuh Orang Tua Dengan Kemandirian Personal Hygiene Anak di Madrasah Ibtidaiyah Negeri 2 Manado - Rukmini Harun; Petronela Mamentu (Jurnal Ventilator, 2023)
Entering elementary school age is a very important time for the continuity of a child's development. Children have many activities that are often directly related to a dirty environment that causes children to be susceptible to disease. Parental support in terms that are very important for children's independence, especially in personal hygiene. The purpose of this study was to find out if there is a relationship between parental parenting and personal hygiene independence in elementary school children in Madrasah Ibtidaiyah Negeri 2 Manado. The design of this study uses a cross sectional approach. . This type of research is observational. The sample in this study was 50 respondents. Respondents with the measuring tool used in this study is questionnaires and then data collected and processed using the SPSS computer program,, to be analyzed using the Chi-square test. The results of the study using the Chi-square test found that the value of p value was less than a significant value (0.01<0.05) the results of this study showed that Ha was accepted and H0 was rejected. The conclusion that can be taken is the parenting of parents have a relationship to personal hygiene independence in elementary school children. The results of this study can be a means of education for parents in improving the independence of children's personal hygiene.